PENGARUH KEPEMILIKAN PENGENDALI TERHADAP TRANSAKSI PIHAK BERELASI YANG DIMODERASI PRAKTEK CORPORATE GOVERNANCE - Adelia Jessika; M Ali Fikri; Zuhrotul Isnaini (Jurnal Riset Akuntansi, 2017)
The objective of this study is to examinethe influence of the direct controlling ownership rights and controlling right, namely right on the cash flow of the related party transactions associated toassets and liabilities. This study also aimed to examine thepractice of corporate governanceas a moderating variablein the relationship between controlling ownership of shareholders and related party transactions associated to assets and debt. Sampling wasdetermined based on purposive samplingin order to obtain a sample companies listedon the Indonesia Stock Exchangeduring 2010 to 2012 with a total 99 of observations. The dependent variablein this study is related party transaction that ismeasured by assets related partyt ransactions and debt related party transactions. The independent variable in this study is ownership controlling, which measured bythe control rights and cash flow rights owned bythe direct controlling ownership of the company. Hypotheses testing based on multiple regression analysis showed that the control rights of shareholders is influence by assets related party transactions and debt related party transactions. Shareholders cash flow right was found to have influence on asset related party transactions but has no influence on debt related Party transactions. The results also show that the corporate governance mechanism isable to moderate the influence of the right ofcontrol over the assets related party transactions and debt related party transactions.